(untitled) (UNED Research Journal, 2022)
Introduction: A prioritization methodology based on bottom-up risks is proposed for different hazards and food matrices. The variables of the model are subdivided into two categories: a) the characteristics of the hazard, where the probability of occurrence and severity are quantified. (b) the properties of the food matrix which estimate its epidemiological risk, presence in the food and vulnerability of its manufacture. A Risk Index (IR) is established as a parameter to facilitate food safety managers to discriminate and prioritize Significant Hazards during the hazard identification of HACCP plans. Objective: The aim of this work was to establish a flexible and dynamic methodology of prioritization based on risk for processing and processing companies of animal products intended for human consumption and integrate it with HACCP plans, allowing specific controls to be established in the production process. Results: The significance values between the clusters Nrp and Nrm were p<0,05. The Spearman Correlation Coefficient (rho) was estimated to determine the proportion of variation between the same predictors. The results obtained were Or-Nrp (rho= 0,719, p= <0,001), Se-Nrp (rho= 0,888, p-valor= <0,001), Re-Nrm (rho= 0,560, p-valor= <0,001), Pm-Nrm (rho= 0,696, p-valor= <0,001) y Vd (rho= 0,687, p-valor= <0,001), respectively. A case study is included to simulate the model and demonstrate its operability. Discussion: The results obtained demonstrate the replicability and validity of this model. The name APIR (Prioritization analysis based on Risk Index) is proposed for this methodology.